The Impact of the 4/3/2 Speaking Technique on EFL Students' Speaking Fluency - Nur Asriayu; Muhammad Yusuf; Nurhamdah; Nurul Hasanah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This study investigated the impact of the 4/3/2 speaking technique on EFL students' speaking fluency at MAN 2 Parepare, Indonesia. The study employed a pre-experimental one-group pre-test and post-test design involving 30 eleventh-grade students. Students' speaking fluency was assessed using an analytical speaking rubric covering speech rate, pauses, self-correction, and overall fluency. The treatment was conducted through six speaking sessions using repeated oral production under decreasing time pressure. The data were analyzed using descriptive statistics, Intraclass Correlation Coefficient (ICC), paired-samples t-test, and effect size analysis. The findings revealed a significant improvement in students' speaking fluency after the treatment. The mean score increased from 6.93 in the pre-test to 8.25 in the post-test, with p < .001. The ICC results also indicated excellent inter-rater reliability. Furthermore, the effect size analysis revealed a large effect (Cohen's d = 0.91). These findings suggest that the 4/3/2 speaking technique effectively improves EFL students' speaking fluency.